Yellow fever and Max Theiler: the only Nobel Prize for a virus vaccine - Norrby, Erling (The Rockefeller University Press, 2007)
In 1951, Max Theiler of the Rockefeller Foundation received the Nobel Prize in Physiology or Medicine for his discovery of an effective vaccine against yellow fever—a discovery first reported in the JEM 70 years ago. This was the first, and so far the only, Nobel Prize given for the development of a virus vaccine. Recently released Nobel archives now reveal how the advances in the yellow fever vaccine field were evaluated more than 50 years ago, and how this led to a prize for Max Theiler.